Ergonomic Evaluation of Hand Tools Injuries among Indian Farmers - Kumar, Adarsh; Singh, J K; Mohan, Dinesh; Varghese, Mathew (Journal of Agricultural Engineering, 2006)
There are 800 million hand tools used on Indian farms by 260 million farm workers. This study was done in survey of two phases. In the first phase, data on agricultural related injuries was collected from nine contiguous villages in a total population of 19,723 persons. In the second phase of study 21 more villages were added and population covered in was 78,890. A total of 576 and 282 agricultural injuries were reported in Phase-I and Phase-II respectively. Hand tools accounted for 332 (58%) and 54 (19%) of total agricultural injuries in the two phases of survey respectively. Most of the injuries i.e. 98% and 91% of the hand tool injuries caused were AIS I (45% and 17% of the total AIS I injuries) in Phase I and II. 70% of AISI hand tool injuries had a recovery time of more than 7 days in Phase I. In phase II, all AIS I injuries took more than 7 days to recover. The mechanism of injuries was slippage of tool from hand or hitting a hard surface in impact type soil interactive tools (spade). The foot and legs were the body part injured most frequently in these tools. In case of harvesting tools (sickle), amputations of fingers and in weeding fork abrasions on under side of little finger because of ground contact were common injuries. In case of axe and sugar cane cutter injuries, higher severity injuries were sustained on upper extremities. There are 1700 injuries related to hand tools per hundred thousand farm workers per year in rural India. Productivity is impaired to the tune of 24,000 days per hundred thousand population because of injuries caused by hand tools on farms.